Radiographic outcome and complications of tibial plateau leveling osteotomy stabilized with an anatomically contoured locking bone plate. Issue 7 (3rd September 2013) - Kowaleski, Michael P.; Boudrieau, Randy J.; Beale, Brian S.; Piras, Alessandro; Hulse, Donald; Johnson, Kenneth A.
Abstract: Objective: To evaluate the short‐term clinical performance of an anatomically pre‐contoured, locking plate in dogs undergoing tibial plateau leveling osteotomy (TPLO) for cranial cruciate ligament (CrCL) disease. Study Design: Prospective, multi‐center clinical study. Animals: Dogs (n = 56) undergoing TPLO. Methods: Signalment and operative data were recorded. Preoperative, postoperative, and follow‐up tibial plateau angle (TPA) were measured from radiographic images. Intraoperative and postoperative complications were recorded; the latter were categorized as minor if additional surgery was not necessary, and major if surgery was needed to resolve the complication. Bone healing was scored and change in tibial plateau angle (TPACH ) between postoperative and follow up radiographic images was calculated. Results: Mean (±SD) preoperative TPA was 28.6 ± 3.8°, and mean postoperative TPA was 4.8 ± 1.9°. Four intraoperative complications (7.1%) including 2 cases of intra‐articular screw placement, 3 minor postoperative complications (5.4%), and no major or catastrophic postoperative complications occurred. Median bone healing grade was 4/4 (excellent union >75% healing). Mean TPACH was 0.15 ± 1.32°. Conclusions: Use of this anatomically contoured, locking TPLO plate by experienced surgeons is associated with accurate tibial plateau leveling, reliably excellent bone union at follow‐up exam, minimal TPACH, and a lower complication rate than previously reported. Confining contouring to the distal shaft of the plate ensures there is precise apposition to the tibial diaphysis and mitigates the risk of intra‐articular screw placement.